2018
DOI: 10.2147/opth.s171576
|View full text |Cite
|
Sign up to set email alerts
|

Implantable collamer lens with central hole: 3-year follow-up

Abstract: PurposeTo evaluate the long-term predictability, stability, safety, and efficacy of the V4c Visian implantable collamer lens (ICL) with central hole to correct myopia.Patients and methodsOne hundred and eighty-four eyes of 92 patients were evaluated during 3 years after implantation of the V4c ICL. The refraction, uncorrected distance visual acuity, best-corrected distance visual acuity, IOP, endothelial cell count, vault, and adverse effects were evaluated every 12 months during the whole follow-up.ResultsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 35 publications
10
43
0
2
Order By: Relevance
“…However, the implantable collamer lens (ICL) is very similar, and there are reports of 10 years of follow-up with the ICL (15,16). Fernández-Vega-Cueto et al (17) found that prior to implantation of the Visian ICL (Staar Surgical AG, Nidau, Switzerland), the mean SE was -8.30±2.98 D; after surgery, it was -0.19±0.32 D, -0.29±0.38 D, and -0.37±0.47 D at 12, 24, and 36 months, respectively. They reported that the regression between the first and third years was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implantable collamer lens (ICL) is very similar, and there are reports of 10 years of follow-up with the ICL (15,16). Fernández-Vega-Cueto et al (17) found that prior to implantation of the Visian ICL (Staar Surgical AG, Nidau, Switzerland), the mean SE was -8.30±2.98 D; after surgery, it was -0.19±0.32 D, -0.29±0.38 D, and -0.37±0.47 D at 12, 24, and 36 months, respectively. They reported that the regression between the first and third years was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The Implantable Collamer Lens (ICL) has becoming more and more commonly used as an effective technique for correcting myopia in recent years [1, 2] . It was designed to be implanted on the ciliary sulcus in the posterior chamber, and far away from corneal endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Vault measurement after ICL implantation is determined to ensure surgical safety. As several parameters affected the vault after surgery [21][22][23][24] and this can change with time [25][26][27][28] , accurate objective measurements are required under different conditions in the short and long terms to understand the dynamic interactions between the ICL and the surrounding structures. The current results suggest that cycloplegic eyedrops have different effects on vault measurements, and several parameters may influence such changes.…”
Section: Discussionmentioning
confidence: 99%